PENGETAHUAN TENTANG KARIES GIGI PADA SISWA KELAS V SDN SUNGGUMINASA 1 TAHUN 2021 - Sangkala, Sangkala; Zulkarnain, Zulkarnain; Nurhaedah, Nurhaedah; Wijaya, Ayu; Alimuddin, Hadijah; Alfah, Siti (Jurnal Ilmiah Amanah Akademika, 2021)
Dental caries is an oral health problem that can affect public health. Dental caries is often experienced by both children and adults. According to 2018 Basic Health Research Results (RISKESDAS) data, in Indonesia currently dental and oral health is still a problem, and the largest proportion of dental problems in Indonesia are cavities at 45.3%, dental caries in school age children occurs due to several factors one of which is children's knowledge about caries, such as what dental caries is, and how dental caries itself occurs. The problem in this research is the high percentage of dental caries among students at SDN Sungguminasa 1 Gowa. The aim of this research is to gain knowledge about the meaning of dental caries, the causes of dental caries, the impact of dental caries, as well as the treatment and prevention of dental caries in class V students at SDN Sungguminasa 1 Gowa. The method used in this research is to fill out a questionnaire via Google Form. The data analysis technique is by calculating the average (mean) in percentage form and presenting it in table form. This type of research is descriptive research. The targets of this research were class V students at SDN Sungguminasa 1 Gowa with a total of 35 students as respondents. The results of this research obtained knowledge about the meaning of dental caries in class V students at SDN Sungguminasa 1 Gowa in the Good category, knowledge about the causes of dental caries in class V students at SDN Sungguminasa 1 Gowa in the good category, knowledge about the impact of dental caries in class V students at SDN Sungguminasa 1 Gowa is in the good category, as well as knowledge about how to treat and prevent dental caries in class V students at SDN Sungguminasa 1 Gowa in the good category. It is hoped that class V students at SDN Sungguminasa 1 Gowa, apart from knowing about dental caries, can also better understand the problem of caries tooth.